Szlachetni szaleńcy czy zwykli złodzieje? Wybrane aspekty problemu kradzieży książek na przestrzeni wieków - Kubiaczyk, Monika (Studia Europaea Gnesnensia, 2020)
This paper analyzes the phenomenon of book theft, sometimes referred to somewhat frivolously as bibliokleptomania. The essential goal is to outline the motives behind such practices and, based on that, develop a typology of book thieves.